Herpes simplex virus 2 and syphilis among young drug users in Baltimore, Maryland. Issue 3 (27th May 2005) - Plitt, S S; Sherman, S G; Strathdee, S A; Taha, T E
Abstract : Objectives: To examine the sex specific seroprevalence and correlates of herpes simplex virus 2 (HSV-2) and syphilis among a cohort of young drug users. Methods: Drug users aged 15–30 years old who used heroin, cocaine, or crack were recruited between October 1999 and August 2002. Baseline interviews gathered information on sociodemographics, drug use and sexual behaviours. Serum was tested at baseline for HSV-2 and syphilis seroreactivity. For each sexually transmitted infection (STI), infected and non-infected participants were stratified by sex and compared using χ 2, Mann-Whitney tests, and logistic regression. Results: Of the 543 participants recruited, 42.4% were female and 39.3% were African-American. The seroprevalence of STIs among females and males, respectively, were HSV-2: 58.7% and 22.0%; syphilis: 4.3% and 0.3%. In multivariate models, older age, African-American race, having over 30 lifetime sex partners, current HIV infection and previous incarceration were independently associated with HSV-2 infection among males. For females, older age, African-American race, sex trade, and daily heroin use were independently associated with HSV-2. For females, only a self reported previous syphilis diagnosis was associated with current syphilis seroreactivity in multivariate analyses. Conclusions: Examination of this cohort revealed a particularly high seroprevalence of HSV-2 and syphilis, especially among female drug users. Few infected participants had been previously diagnosed with these infections.